Relatório de Estágio: Treino de Força e Multicomponente nos idosos - José Pedro Dias Baptista (2020)
This internship report was carried out within the scope of the 2nd Cycle in Physical Activity for the Elderly at the Faculty of Sports of the University of Porto and aims to present and reflect on the work developed in the academic year of 2019/2020. In this document we show the planning, the application and the reflection of the annual activities, of the results obtained in 5 groups, each one in different contexts, inserted (or in collaboration) in the Mais Ativos Mais Vividos program, carrying out specific strength training (2 classes of apparently healthy elderly in the community), Multicomponent Training (2 classes of the elderly in the community: FADEUP and "Trajetórias" project) and with elderly people with dementia (1 class). Succeeding an initial assessment of physical fitness through the Senior Fitness Test battery (Rikli and Jones, 1999), in October, the training prescription developed in the different programs was carried out according to the recommendations for the physical activity for the elderly (Riebe D. et al., 2018). Until March 2020, the training sessions took place at the Faculty of Sports of the University of Porto, the Social Center of Oliveira do Douro and at the Socio-Cultural Center of Foz do Douro. Between March and June, the world pandemic that followed this academic year, forced the interruption of classes, however, videos of physical activity sessions at home have been made available. Nevertheless, given the context of the COVID-19 pandemic, it was only possible to carry out the final physical fitness assessments, in June, in the weight training and multicomponent training classes of the elderly residents in the community. In general, results showed that these elderly people maintained, overall, the results of the initial physical fitness assessment. This demonstrates that despite the stoppage of the sessions, the students continued with an active lifestyle.